Eight new species of Dexosarcophaga Townsend, 1917 (Diptera, Sarcophagidae) from the Neotropical Region - dos Santos, Josenilson Rodrigues; Pape, Thomas; de Mello-Patiu, Cátia Antunes (European Journal of Taxonomy, 2022)
Eight new Neotropical species of Dexosarcophaga Townsend, 1917 are described, five from Brazil, Dexosarcophaga phoenix sp. nov., Dexosarcophaga jandainae sp. nov., Dexosarcophaga patiuorum sp. nov., Dexosarcophaga petra sp. nov., and Dexosarcophaga sphaera sp. nov., one from Costa Rica, Dexosarcophaga limon sp. nov., one from Ecuador, Dexosarcophaga napo sp. nov., and one from Colombia, Dexosarcophaga pallida sp. nov. Male and female morphology is documented with photographs and illustrations, including details of the male terminalia for all new species and female terminalia of Dexosarcophaga phoenix sp. nov. and Dexosarcophaga sphaera sp. nov. With the addition of these new species, 58 species of Dexosarcophaga are now known, with records from the American continent spanning from the southern United States to northern Argentina.